Effect of probiotic supplementation on migraine prophylaxis: a systematic review and meta-analysis of randomized controlled trials. (4th March 2022) - Parohan, Mohammad; Djalali, Mahmoud; Sarraf, Payam; Yaghoubi, Sajad; Seraj, Asal; Foroushani, Abbas Rahimi; Ranji-Burachaloo, Sakineh; Javanbakht, Mohammad Hassan
ABSTRACT: Objective: The prevalence of migraine is higher in patients with gastrointestinal disorders. Possible underlying mechanisms could be increased intestinal permeability and systemic inflammation. Probiotics may reduce gut permeability as well as inflammation, and therefore may improve the clinical features of migraine. This systematic review and meta-analysis aimed to evaluate the impact of probiotic supplementation on the frequency and severity of migraine attacks. Methods: A systematic review of the literature was conducted using ISI Web of Science, PubMed/Medline, Scopus, Cochrane Library, EMBASE, Google Scholar, Magiran.com and Sid.ir to identify eligible studies published up to October 2019. A meta-analysis of eligible trials was performed using the random-effects model to estimate pooled effect size. Results: Three randomized controlled trials with 179 patients (probiotic group = 94, placebo group = 85) were included. Probiotic supplementation had no significant effect on frequency (weighted mean difference (WMD) = −2.54 attacks/month, 95%CI: −5.31–0.22, p  = 0.071) and severity of migraine attacks (WMD = −1.23 visual analog scale (VAS) score, 95%CI = −3.37–0.92, p  = 0.262) with significant heterogeneity among the studies ( I 2  = 98%, p  < 0.001). Conclusions: A pooled analysis of available randomized controlled clinical trials showed that probiotic supplementation had no significant effect on the frequency and severity of episodic migraine attacks.